English Deficiency and the Native-Immigrant Wage Gap - Alfonso Miranda; Yu Zhu (University of Kent, School of Economics, 2012)
We focus on the effect of English deficiency on the native-immigrant wage gap for employees in the UK using the first wave of the UK Household Longitudinal Survey (Understanding Society). We show that the wage gap is robust to controls for age, region of residence, educational attainment and ethnicity, particularly for men. However, English as Additional Language (EAL) is capable of explaining virtually all the remaining wage gap between natives and immigrants. Using the interaction of language of country of birth and age-at-arrival as instrument, we find strong evidence of a causal effect of EAL on the native-immigrant wage gap.
Keywords: J15; J61; 330; native-immigrant wage gap; English as Additional Language (EAL); age-at-arrival; Migranten; Lohnstruktur; Englisch (Sprache); Mehrsprachigkeit; Großbritannien